Microplastic pollution in tropical estuary gastropods: abundance, distribution and potential sources of Klang River estuary, Malaysia - Mohd Zaki, Muhammad Rozaimi; Mohamad Zaid, Syatirah Husna; Zainuddin, Azim Haziq; Aris, Ahmad Zaharin (Elsevier, 2021)
Microplastics receive global attention due to its strong presence in marine and freshwater organisms. Yet, there are few studies on estuarine organisms. This baseline study evaluates the abundance and distribution of microplastics in the gastropods of a tropical estuary in Selangor, Malaysia. The abundance of microplastics ranged from 0.50 to 1.75 particles/g or from 0.25 to 0.88 particles/individual. The variation in microplastic distribution between the upper and lower estuary indicates that the microplastics originated from the urbanised area of the Klang River estuary. Microplastic sizes varied from 30 to 1850 μm, with the majority being between 300 and 1000 μm (57%). Characteristics of microplastics were dominant for fibres (91%) with black colour (50%). Polyethylene-propylene-diene (PE-PDM) and polyester were the main polymer materials. Assessing the contamination of gastropods by microplastics provides insight into the possibility of utilising gastropods as bioindicators that could be used for monitoring and baseline studies.